2011
DOI: 10.3109/13693786.2011.576350
|View full text |Cite
|
Sign up to set email alerts
|

Identification of allergens homologous to Alt a 1 fromStemphylium botryosumandUlocladium botrytis

Abstract: Several studies have demonstrated that proteins homologous to the Alt a 1 major allergen of Alternaria alternata are expressed in other members of the Pleosporaceae family. However, since no direct biochemical data have been reported concerning the presence of Alt a 1 allergen homologues capable of binding IgE in the excretion-secretion products of Stemphylium and Ulocladium, our objective was to explore their presence in Stemphylium botryosum and Ulocladium botrytis. S. botryosum and U. botrytis culture filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…alternata in 10.7% of our samples with culturing and 27.3% with DNA sequencing . However, we cannot exclude a possibility that this metabolite might be also produced by other members of the Pleosporales of which we identified a broad diversity using DNA sequencing . Nine metabolites (3‐nitropropionic acid, asperglaucide, chlorocitreorosein, citreorosein, emodin, linamarin, lotaustralin, physcion and tryptophol) could be derived from plants and fungi .…”
Section: Discussionmentioning
confidence: 92%
“…alternata in 10.7% of our samples with culturing and 27.3% with DNA sequencing . However, we cannot exclude a possibility that this metabolite might be also produced by other members of the Pleosporales of which we identified a broad diversity using DNA sequencing . Nine metabolites (3‐nitropropionic acid, asperglaucide, chlorocitreorosein, citreorosein, emodin, linamarin, lotaustralin, physcion and tryptophol) could be derived from plants and fungi .…”
Section: Discussionmentioning
confidence: 92%
“…Alternaria spp., along with other species belonging to the order Pleosporales, including Pleospora and Ulocladium species, produce the major allergen Alt a 1 or a similar homolog, sometimes in greater quantities than A. alternata . 3638,41 Alt a 1 has been shown to be recognized by human immunoglobulin E in over 80% of Alternaria -sensitized individuals 42,43 and previous studies have demonstrated that 85% of Alternaria -sensitized individuals had positive skin test reactivity to recombinant Alt a 1. 44,45 Individuals in EC environments are likely exposed to Alt a 1, or another homologous allergen, increasing susceptibility to fungal sensitization.…”
Section: Discussionmentioning
confidence: 96%
“…This is a particularly important risk factor for fungal sensitized populations as fungi placed in this order are among the most frequently encountered fungal sensitizers and contain allergens that are homologous with A. alternata . 3638 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found homologues of Alt a 1 in the phylogenetically related Stemphylium and Ulocladium species. This suggests that Alt a 1 may not be species-specifi c (47,48). Several other A. alternata allergens have shown significant cross-reactivity with a closely related mould C. herbarum and with non-fungal species (47).…”
Section: Allergens Of a Fumigatus And A Alternatamentioning
confidence: 99%
“…are also important sources of allergens for mould-allergic patients (33). Cross-reactivity between the most common allergenic moulds has been presented elsewhere (47)(48)(49)(50)(51).…”
Section: Allergens Of a Fumigatus And A Alternatamentioning
confidence: 99%